Cracking The Code: Bilateral Optic Disc Swelling With Serous Retinal Detachment As A Clue Of Vogt-koyanagi-harada Disease - Saraswati, Sani Ratna; Aryawan, I Ketut (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Vogt–Koyanagi–Harada disease (VKH) is a rare autoimmune disorder that attacks melanocyte-containing tissues, particularly the eyes, and can involve the central nervous system, hearing, and skin. VKH is one of the leading causes of non-infectious panuveitis in pigmented populations, and delayed diagnosis can lead to permanent visual impairment. Therefore, early detection and appropriate corticosteroid therapy are crucial to prevent long-term visual impairment. The purpose of this case report is to describe the clinical manifestations, supporting examinations, and response to high-dose corticosteroid therapy in a patient with suspected VKH disease. Case Illustration: A 39-year-old male presented with one week of progressive bilateral visual loss accompanied by fever, headache, and tinnitus. Examination revealed anterior chamber cells and flare, optic disc swelling, and serous retinal detachment. Optical coherence tomography confirmed subretinal fluid with septa formation. The patient was treated with high-dose intravenous methylprednisolone followed by oral tapering, resulting in significant visual improvement and stable recovery over one year. Conclusion: Early recognition of VKH disease and prompt initiation of high-dose corticosteroid therapy are crucial to control inflammation, prevent recurrences, and preserve long-term visual function.